Public Health Challenges and Responses to the Growing Ageing Populations - Hafiz T. A. Khan; Kwaku Mari Addo; Helen Findlay (Wiley, 2024)
ABSTRACT Background Human populations are rapidly ageing worldwide due to declining birth rates and rising life expectancies. This profound demographic shift presents complex public health challenges. Synthesizing evidence on key public health issues impacting ageing populations and policy strategies is required to address these needs. Methods The study employs narrative literature review based on the PubMed database. Data have been extracted on public health challenges to ageing populations and its recommended policy solutions. Results The key public health challenges identified include rising chronic disease burden, risks for preventable multi‐morbidities and co‐morbidities, disability and dependencies, mental health issues, caregiving gaps, long‐term care system deficiencies, health inequities, healthcare access barriers, end‐of‐life care needs, financial instability, ageism/elder abuse, adverse built environments, climate/disaster threats, and social isolation. Evidence‐based policy responses span interventions in healthcare, social services, urban planning, emergency preparedness, economics, technology, anti‐ageism advocacy and so on. Conclusions Proactively addressing the array of public health challenges faced by rapidly growing ageing populations globally requires implementing collaborative, multisectoral policy solutions focused on promoting healthy, equitable, and socially engaged ageing. Healthcare systems, communities, and policies must be optimized to meet the needs of elderly people and tap into their strengths.